Study on Optimal Design for Synchronizer - Zhang Yong; Huang Mingli; Wu Xuncheng; Zhang Juecheng; Zhang Tao (Jixie chuandong)
The synchronizer is an essential part of the manual transmission. The reference for synchronizer design is provided by studying optimization design of synchronizer. A mathematical model of lock ring synchronizer contact wear and optimization mathematical model with synchronizer life as the objective function are established based on principles of tribology and Majundar- Bhushan fractal theory. The optimization mathematical model is solved by APSO（ Adaptive particle swarm optimization） and the synchronizer life has greater increase than before optimization.